2005
DOI: 10.1038/sj.hdy.6800750
|View full text |Cite
|
Sign up to set email alerts
|

Male sterility in triploid dandelions: asexual females vs asexual hermaphrodites

Abstract: Male reproductive output, pollen in plants and sperm in animals has been shown to constitute a substantial cost for many organisms. In parthenogenetic hermaphrodites, selection is therefore expected to reduce the allocation of resources to male reproductive output. However, sustained production of pollen or sperm has been observed in numerous asexual hermaphrodites. We studied the widespread production of pollen by triploid asexual dandelions, Taraxacum sect. Ruderalia, comparing rare male sterile individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
0
28
0
2
Order By: Relevance
“…This is not unexpected as r was in fact developed to be independent both of the ploidy level and the amount of within-individual diversity; it is therefore also independent of the amount of selfing and double reduction. Although this statistic is not very widely used (but see Hardy and Vekemans, 2001;Meirmans et al, 2006), we recommend the use of r for any study of population structure in polyploids, especially when the exact mode of inheritance is unknown. However, it is important to realise that the interpretation of r is different than that of F ST : r gives consistently higher values than F ST (Ronfort et al, 1998).…”
Section: Estimating Population Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexpected as r was in fact developed to be independent both of the ploidy level and the amount of within-individual diversity; it is therefore also independent of the amount of selfing and double reduction. Although this statistic is not very widely used (but see Hardy and Vekemans, 2001;Meirmans et al, 2006), we recommend the use of r for any study of population structure in polyploids, especially when the exact mode of inheritance is unknown. However, it is important to realise that the interpretation of r is different than that of F ST : r gives consistently higher values than F ST (Ronfort et al, 1998).…”
Section: Estimating Population Divergencementioning
confidence: 99%
“…For real data this is not possible and the statistics are inferred from estimated allele frequencies in marker data. For polyploids, it can be hard to obtain the dosage of the alleles from, for instance, the band intensities (for example, Meirmans et al, 2006), especially for higher ploidy levels (Clark and Jaseniuk, 2011). This can lead to a bias in the estimation of allele frequencies and hence the degree of population differentiation.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…For instance, Meirmans et al (2006) found that male-sterile apomictic dandelions (Taraxacum sect. Ruderalia) produce more flower heads per plant, and thus more seeds, than pollen-producing apomicts.…”
Section: Variation In Pollen Productionmentioning
confidence: 99%
“…This is commonly observed within the Taraxacum genus (Małecka 1971a(Małecka , 1973Van Baarlen et al 2000;Marciniuk et al 2010a;Musiał et al 2013a). Maynard Smith (1978) suggested that apomicts producing pollen are phylogenetically relatively young to have accumulated the necessary mutations that cause male sterility. However, male sterility has been found in both diploid sexual and apomictic dandelions representing numerous sections (Van Soest 1965;Richards 1970;Małecka 1971b; Van der Hulst et al 2004;Meirmans et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies, as well as the present observations of the ovule anatomy and female gametophyte structure in T. belorusscium, clearly indicate that, although in apomictic dandelions the development of both embryo and endosperm is autonomous, their ovules and unreduced female gametophytes permanently retain features that are associated with sexual reproduction. This can be explained by the fact that apomictic Taraxacum species are considered to be relatively recent in origin and hence the functionless characters are still maintained (Richards 1973;Maynard Smith 1978;Van Dijk 2003). On the other hand, Płachno et al (2015) pointed out that the presence of vital micropylar transmitting tissue and synergid cells with a filiform apparatus makes no barrier for pollen tube to reach the ovule and female gametophyte, thus fertilization of an unreduced egg cell of apomicts is likely, which may be essential in the light of possible hybridization among sexuals and apomicts and the creation of new apomictic lineages, advantageous from an evolutionary point of view.…”
Section: Discussionmentioning
confidence: 99%